Responses of midgut amylases of Helicoverpa armigera to feeding on various host plants - Kotkar, Hemlata M.; Sarate, Priya J.; Tamhane, Vaijayanti A.; Gupta, Vidya S.; Giri, Ashok P. (Journal of Insect Physiology, 2009)
Midgut digestive amylases and proteinases of Helicoverpa armigera, a polyphagous and devastating insect pest of economic importance have been studied. We also identified the potential of a sorghum amylase inhibitor against H. armigera midgut amylase. Amylase activities were detected in all the larval instars, pupae, moths and eggs; early instars had lower amylase levels which steadily increased up to the sixth larval instar. Qualitative and quantitative differences in midgut amylases of H. amigera upon feeding on natural and artificial diets were evident. Natural diets were categorized as one or more members of legumes, vegetables, flowers and cereals belonging to different plant families. Amylase activity and isoform patterns varied depending on host plant and/or artificial diet. Artificial diet-fed H. armigera larvae had comparatively high amylase activity and several unique amylase isoforms. Correlation of amylase and proteinase activities of H. armigera with the protein and carbohydrate content of various diets suggested that H. armigera regulates the levels of these digestive enzymes in response to macromolecular composition of the diet. These adjustments in the digestive enzymes of H. armigera may be to obtain better nourishment from the diet and avoid toxicity due to nutritional imbalance. H. armigera, a generalist feeder experiences a great degree of nutritional heterogeneity in its diet. An investigation of the differences in enzyme levels in response to macronutrient balance and imbalance highlight their importance in insect nutrition. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: Amylase inhibitors; Diet; Helicoverpa armigera larvae; Midgut amylase; Proteinases

Biochemical characterisation of alpha-amylase inhibitors from achyranthes aspera and their interactions with digestive amylases of coleopteran and lepidopteran insects - Hivrale, Vandana K.; Chougule, Nanasaheb P.; Giri, Ashok P.; Chhabda, Pavan J.; Kachole, Andmanvendra S. (Journal of the Science of Food and Agriculture, 2011)
BACKGROUND: Starchy seeds are an important food and a source of dietary ingredients in many countries. However, they suffer from extensive predation by bruchids (weevils) and other pests. alpha-Amylase inhibitors are attractive candidates for the control of seed weevils, as these insects are highly dependent on starch as an energy source. RESULTS: A proteinaceous alpha-amylase inhibitor from the seeds of Achyranthes aspera was identified, purified and characterised. In electrophoretic analysis, two prominent amylase inhibitor activity bands (AI1 and AI2) were detected. The inhibitor was purified 9.99-fold with 1206.95 total amylase inhibitor units mg(-1) protein. The molecular weight of the purified inhibitor was around 6 kDa. The isolated alpha-amylase inhibitor was found to be resistant to heat and proteolysis. Feeding analysis of Callosobruchus maculatus larvae on a diet containing seed powder of A. aspera revealed that survival of the larvae was severely affected, with the highest mortality rate occurring on the fifth day of feeding. The isolated inhibitor inhibited the majority of amylase isoforms of C. maculatus, Tribolium confusum and Helicoverpa armigera in electrophoretic analysis and solution assays. CONCLUSION: The information obtained in the present investigation could be useful for a genetic engineering approach that would make seeds resistant to storage pest infestations. (C) 2011 Society of Chemical Industry
Keywords: Achyranthes aspera; Amylase inhibitors; amylases; Callosobruchus maculatus; Tribolium confusum

Biochemical, structural and functional diversity between two digestive alpha-amylases from helicoverpa armigera - Bhide, Amey J.; Channale, Sonal M.; Patil, Sucheta S.; Gupta, Vidya S.; Ramasamy, Sureshkumar; Giri, Ashok P. (Biochimica Et Biophysica Acta-General Subjects, 2015)
Background: Helicoverpa armigera (Lepidoptera) feeds on various plants using diverse digestive enzymes as one of the survival tool-kit. The aim of the present study was to understand biochemical properties of recombinant alpha-amylases of H. armigera viz., HaAmy1 and HaAmy2. Methods: The open reading frames of HaAmy1 and HaAmy2 were cloned in Pichia pastoris and expressed heterologously. Purified recombinant enzymes were characterized for their biochemical and biophysical attributes using established methods. Results: Sequence alignment and homology modeling showed that HaAmy1 and HaAmy2 were conserved in their amino acid sequences and structures. HaAmy1 and HaAmy2 showed optimum activity at 60 degrees C; however, they differed in their optimum pH. Furthermore, HaAmy2 showed higher affinity for starch and amylopectin whereas HaAmy1 had higher catalytic efficiency. HaAmy1 and HaAmy2 were inhibited to the same magnitude by a synthetic amylase inhibitor (acarbose) while wheat amylase inhibitor showed about 2-fold higher inhibition of HaAmy1 than HaAmy2 at pH 7 while 6-fold difference at pH 11. Interactions of HaAmy1 and HaAmy2 with wheat amylase inhibitor revealed 2:1 stoichiometric ratio and much more complex interaction with HaAmy1. Conclusions: The diversity of amylases in perspective of their biochemical and biophysical properties, and their differential interactions with amylase inhibitors signify the potential role of these enzymes in adaptation of H. armigera on diverse plant diets. General significance: Characterization of digestive enzymes of H. armigera provides the molecular basis for the polyphagous nature and thus could assist in designing future strategies for the insect control. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: alpha-amylases; Amylase inhibitors; Digestive enzymes; Enzyme activity; Helicoverpa armigera

Improvement in serum amylase and glucose levels in diabetic rats on oral administration of bisdemethoxycurcumin from Curcuma longa and limonoids from Azadirachta indica - Ramkumar, Sudha; Thulasiram, V. H.; RaviKumar, Ameeta (Journal of Food Biochemistry, 2021)
Curcuma longa and Azadirachta indica are traditionally used in Indian cuisine and Ayurvedic medicine as nutraceuticals against diabetes. The crude C. longa isopropanol extract, bisdemethoxycurcumin (BDMC), the purified bioactive component from C. longa, and limonoids azadiradione, gedunin from A. indica, are able to inhibit in vitro the antidiabetic target human pancreatic alpha-amylase independently. However, no reports on their in vivo efficacy in animal models exist. Thus, the antidiabetic effect of these orally administered human pancreatic alpha-amylase inhibitors was performed on streptozotocin-induced Sprague-Dawley rats. Initially, the normal rats were treated with test compounds (10-100 mg/kg of body weight) in corn oil (5 ml/kg), and as no lethality was observed in these doses, further studies were carried out with lowest concentration of 10 mg/kg of body weight. A reduction in area under curve (AUC) suggested glucose-lowering effect of these compounds in starch fed diabetic rats. The efficacy study showed a significant improvement in body weight, blood glucose levels, serum amylase, and fructosamine levels as well in other serum parameters associated with diabetes with respect to liver and renal functions. Hence, under in vivo conditions, inhibition of alpha-amylase activity by BDMC and limonoids affirms it as one of the mechanisms of action resulting in reduction of blood glucose levels. Practical applications Bisdemethoxycurcumin from C. longa and limonoids, namely, azadiradione and gedunin, from A. indica are potent inhibitors of the antidiabetic target human pancreatic alpha-amylase. Oral Starch Tolerance Test (OSTT) and 28-day efficacy study to check the effect of these orally administered inhibitors in diabetic rat models showed significant improvements in serum blood glucose and amylase levels as well as in other diabetes related serum parameters, namely, bilirubin, lipids, lactate dehydrogenase, alkaline phosphatase, and urea. The study contributes to understanding the action and efficacy of these pancreatic alpha-amylase inhibitors and suggests a potential role for them as nutraceuticals/therapeutics in management of post-prandial hyperglycemia.
Keywords: ‐ α Amylase inhibitors; Azadiractha indica; BDMC; Curcuma longa; in vivo rat studies; Limonoids